(untitled) (Archives of Pediatrics of Uruguay, 2023)
Objective: describe the characteristics of 8 children who presented Multisystem Inflammatory Syndrome associated with SARS-CoV2 infections (MIS-C) and cardiac involvement. Material and methods: descriptive, retrospective study of 8 patients of between 1 and 13 years of age, diagnosed with MIS-C and cardiac involvement, assisted at the Pereira Rossell Children Hospital, analysis of their medical records, evolution and treatment. Results: the patients showed: fever in 100% of the cases, rash and conjunctival hyperemia in 88%, digestive symptoms in 50%, respiratory failure in 25% and shock in 50%. All required admission to Intensive Care. Cardiac contractility alteration was present in 63% of patients, the affectation was mild and segmental in 80%, 60% required inotropic support for 3 days and recovered normal functions in 7 days. Mitral regurgitation was present in 25% of the cases and pericardial effusion in 38%, mild in both cases. One patient had dilated coronary arteries with a Z score <2. 85% of the patients presented ECG abnormalities, 29% present alteration of repolarization, 29% prolonged QTc, 15% 1st degree atrioventricular block and incomplete right bundle branch block. One patient had atrial fibrillation for 3 days with spontaneous remission to sinus rhythm. Troponins were increased in 57% of the patients and ProBNP elevated in 100%. All patients received Immunoglobulins, Methylprednisolone and Aspirin. Conclusions: we present eight pediatric patients with MIS-C and cardiac involvement, 50% suffered shock, all required admission to Intensive Care. ECG abnormalities were found in 85% of the patients. Mild and segmental contractility compromise was found in 63% of the patients and normalized in 7 days. 60% required inotropic support for a mean of 3 days.